2010
DOI: 10.1177/1934578x1000501220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antiviral Activities of Curcumin Derivatives against HSV-1 in Vero Cell Line

Abstract: Antiviral drug resistance is one of the most common problems in medicine, and, therefore, finding new antiviral agents, especially from natural resources, seems to be necessary. This study was designed to assay the antiviral activity of curcumin and its new derivatives like gallium-curcumin and Cu-curcumin on replication of HSV-1 in cell culture. The research was performed as an in vitro study in which the antiviral activity of different concentrations of three substances including curcumin, Gallium-curcumin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 19 publications
2
66
0
Order By: Relevance
“…The 50% cytotoxic concentration (CC 50 ) of the respective compounds on Vero cell line showed to be 484.2  μ g/mL, 255.8  μ g/mL, and 326.6  μ g/mL, respectively [31]. Curcumin considerably decreased the immediate early (IE) gene expression and infectivity of HSV-1 in cell culture assays.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…The 50% cytotoxic concentration (CC 50 ) of the respective compounds on Vero cell line showed to be 484.2  μ g/mL, 255.8  μ g/mL, and 326.6  μ g/mL, respectively [31]. Curcumin considerably decreased the immediate early (IE) gene expression and infectivity of HSV-1 in cell culture assays.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…In another study, curcumin was shown to improve the activity of common azole and polyene anti-fungals (65). In some cell culture systems, curcumin has been shown to possess anti-viral activities (63, 64). Other common activities of curcumin as demonstrated in in vitro cell culture models are wound healing in skin fibroblasts (66), anti-nociceptive activity in ganglion neurons (67), anti-parasitic activity against African trypanosomes (68), schistosomicidal activity against Schistosoma mansoni adult worms (69), anti-malarial activity (70), and nematocidal activity (71).…”
Section: Biological Activities Of Curcuminmentioning
confidence: 99%
“…Treating viral infections is usually a challenging task because viruses are capable of continuous evolution producing drug‐resistant mutants which renders antiviral drugs as ineffective. Although there are recent significant advances in immunization and drug discovery of antiviral drugs, many viruses still lack effective vaccines and antiviral remedies . Thus, the discovery of novel antivirals drugs with high efficacy is highly recommended …”
Section: Introductionmentioning
confidence: 99%